ANALISIS PENAFSIRAN TERHADAP Q.S AL-MA’IDAH: 38 DALAM QUR’AN: A REFORMIST TRANSLATION: (A Reformist Translation) - Ulummudin (QOF, 2019)
Edip Yuksel and his colleages considered Qur’an: A Reformist Translation as a progressive work which is different from previous translation in English. One of the verses of the Qur’an that is often misunderstood is QS. al-Ma’idah (5): 38. The verse talks about the punishment for a burglar. All of translator interpret fakt }a’u aidiyahuma > by cutting off hands. However, Yuksel writes different meaning on it. Therefore, this article explains Yuksel’s opinion on the meaning of qata’a in QS. alMa’idah (5): 38 and then, it is analyzed by three functions theory of Gracia namely historical function, meaning function, and implicative function. Word “Qata’a” in the verse, according to Yuksel has three meanings. They are cut or mark hands, cut off hands, and cut off means. Based on analysis by the theory, first, historical function is not used to determine the meaning of the verse because Yuksel denies the elements of out of the Qur’an such as hadis and sirah. Second, the meaning function is Yuksel presents both literal translation and intended meaning. The literal translation is cut off hands, while the intended meaning is cut or mark hands and cut off means. Literal translation is based on intratexts analysis, whereas intended meaning is considering contemporary context. Third, the implicative function is punishments for a burglar other than cutting off hands are acceptable and do not deviate from the original meaning of the verse. The community can choose the most appropriate type of punishment.